A Case Report of Behavioural Refinement in a Child Suffering from Attention-Deficit Hyperactivity Disorder Using Individualised Homoeopathic Medicine - Singh, Pravin Kumar; Naaz, Sabiha (Homœopathic Links, 2022)
Background Attention-deficit hyperactivity disorder (ADHD) is the commonest juvenile psychiatric disorder distinguished by symptoms of inattention, hyperactivity and impulsivity. ADHD is a serious public health concern because it has a long-term negative impact on academic, career and social-emotional development, thereby hampering the quality of life of the individual. Owing to the prolonged, expensive and ambiguous treatment, an increasing number of parents turn towards homeopathy for safe and cost-effective treatment of their ‘trouble-makers’ as they are labeled.Method A 7-year-old child diagnosed with ADHD (combined type) and patent ductus arteriosus (PDA) uncomplicated with other psychiatric comorbidity presented to the outpatient department after having consulted various physicians in succession in search of effective treatment. The child received individualised homoeopathic medicine. Outcome was measured using the parent completed Conners' Parent Rating Scale-Revised-Short version (CPRS:R-S) every 4 months.Results At the start of the treatment, the child's CPRS:R-S score was 76 which was very high. After a year, it was reduced to eight (within normal range).Conclusion This case demonstrates the usefulness of individualised homoeopathic treatment in improving the ADHD status over a span of 1 year. Nevertheless, large sample randomised controlled trials would be required to approve or disprove this single case observation.
Keywords: case report; ADHD; homoeopathy; individualised medicine; Tuberculinum bovinum